Camouflaged Marriage Annulment: Harmonizing Al-Juwainī’s Fiqh and Religious Court Jurisprudence - Lana Aufa Izza Muhammad; Fitrohtul Khasanah; Najih Abqori; Muhamad Mustahal; Mohammad Chaedar (Al-Mujtahid: Journal of Islamic Family Law, 2026)
Camouflaged marriage annulment raises an important issue in contemporary Islamic family law because a marriage contract may appear formally valid while being used to conceal motives that contradict the purposes of marriage. This study examines how Imam Al-Juwainī’s thought on intention, honesty, and contractual validity can be harmonized with the jurisprudence of the Religious Court in marriage annulment cases. It focuses on Purworejo Religious Court Decision No. 157/Pdt.G/2024/PA.PWR. Using a qualitative method with a normative-empirical approach, this study combines textual analysis of Al-Juwainī’s Nihāyat al-Maṭlab with document analysis of court decisions and relevant Indonesian marriage law. The findings show that, in Al-Juwainī’s legal reasoning, the validity of a marriage contract depends not only on formal pillars and conditions, but also on the conformity of intention with maqāṣid al-nikāḥ. A concealed intention that defeats the purpose of marriage may therefore undermine the legitimacy of the contract. The court decision similarly treats deception, honesty, and the sacred purpose of marriage as central grounds for annulment. This study argues that classical fiqh and contemporary Religious Court jurisprudence can converge to protect substantive justice and preserve the moral objectives of marriage in Islamic family law.